Works. - Mao, Zedong, 1893-1976, author. Link
1 online resource (1 volume)
Keywords: The series, Mao's Road to Power, consisting of translations of Mao Zedong's writings from 1912 to 1949, provides abundant documentation in his own words on his life and thought as well as on developments in China during the pre-1949 period. This penultimate volume in the series, Volume 9, covers the period from the Japanese Surrender through the Chinese Communist Party's Strategic Defense during the Civil War, August 1945 to June 1947.